Liquid biopsy for diagnostic and prognostic evaluation of melanoma - Slusher, Nicholas; Jones, Nicholas; Nonaka, Taichiro (Frontiers in Cell and Developmental Biology, 2024)
Melanoma is the most aggressive form of skin cancer, and the majority of cases are associated with chronic or intermittent sun exposure. The incidence of melanoma has grown exponentially over the last fifty years, especially in populations of fairer skin, at lower altitudes and in geriatric populations. The gold standard for diagnosis of melanoma is performing an excisional biopsy with full resection or an incisional tissue biopsy. However, due to their invasiveness, conventional biopsy techniques are not suitable for continuous disease monitoring. Utilization of liquid biopsy techniques represent substantial promise in early detection of melanoma. Through this procedure, tumor-specific components shed into circulation can be analyzed for not only diagnosis but also treatment selection and risk assessment. Additionally, liquid biopsy is significantly less invasive than tissue biopsy and offers a novel way to monitor the treatment response and disease relapse, predicting metastasis.